Pengaruh Motivasi Kerja, Loyalitas Kerja Dan Komitmen Kerja Terhadap Kinerja Pengawai (ULP Kepulauan Kangean Kabupaten Sumenep) - Mohammad Riyanto; Hadi Sunaryo; Muhammad Ridwan Basalamah (UNIVERSITAS ISLAM MALANG, 2022)
ABSTRACTThis study includes 1) work motivation, work loyalty, work commitment, and an overview of employee performance, 2) work motivation, work loyalty, and the effect of work commitment on employee performance, 3). The aim is to determine the effect of work motivation on employee performance. 4) The effect of work loyalty on employee performance. Employee performance, 5) Impact of work commitment on employee performance.This study uses quantitative methods with descriptive analysis and inference. The number of samples used were 39 respondents from ULP Kangean Islands, Sumenep Regency. Sources of data used are primary and secondary sources. Using a questionnaire with a Likert scale measurement while the analysis used is an instrumental test, classical assumption test, multiple linear regression analysis, hypothesis testing, and coefficient of determination (R2) using SPSS 16.0 tools and data collection. The results of this survey show that 1) work motivation, work loyalty, and commitment affect employee performance simultaneously, 2) work motivation affects employee performance, and 3) work shows that loyalty affects employee performance, 4). Commitment has an impact on employee performance. Employee performance. Keyword : Work Motivation, Work Loyalty , Work Commitment and Employee Perfomance